2008
DOI: 10.1111/j.1365-2125.2008.03236.x
|View full text |Cite
|
Sign up to set email alerts
|

Red ginseng for treating erectile dysfunction: a systematic review

Abstract: Collectively these RCTs provide suggestive evidence for the effectiveness of red ginseng in the treatment of erectile dysfunction. However, the total number of RCTs included in the analysis, the total sample size and the methodological quality of the primary studies were too low to draw definitive conclusions. Thus more rigorous studies are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(140 citation statements)
references
References 25 publications
2
135
0
3
Order By: Relevance
“…A recent systematic review provided evidence for the effectiveness of red ginseng in the treatment of ED from six randomized clinical trials. 18 Although there were some limitations in the sample sizes and the methodological qualities of the primary studies, 18 this meta-analysis found a significant effect of the tested herbal medicine (n5349, risk ratio52.40, 95% CI51.65-3.51, P,0.00001, heterogeneity: t 2 50.05, x 2 56.42, P50.27, I 2 522%). Subgroup analyses also showed beneficial effects of red ginseng in psychogenic ED (n5135, risk ratio52.05; 95% CI51.33-3.16, P50.001, heterogeneity: x 2 50.08, P50.96, I 2 50%).…”
Section: Pro-erectile Effects Of Ginseng Berry Ks Cho Et Al 505mentioning
confidence: 79%
“…A recent systematic review provided evidence for the effectiveness of red ginseng in the treatment of ED from six randomized clinical trials. 18 Although there were some limitations in the sample sizes and the methodological qualities of the primary studies, 18 this meta-analysis found a significant effect of the tested herbal medicine (n5349, risk ratio52.40, 95% CI51.65-3.51, P,0.00001, heterogeneity: t 2 50.05, x 2 56.42, P50.27, I 2 522%). Subgroup analyses also showed beneficial effects of red ginseng in psychogenic ED (n5135, risk ratio52.05; 95% CI51.33-3.16, P50.001, heterogeneity: x 2 50.08, P50.96, I 2 50%).…”
Section: Pro-erectile Effects Of Ginseng Berry Ks Cho Et Al 505mentioning
confidence: 79%
“…We used this range when determining the daily dose of TMGE for our study. Many earlier studies applied ginseng or red ginseng treatment for 4-12 weeks [7]. The duration of treatment within the preliminary study conducted by Kim et al [8] was 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Korean ginseng (Panax ginseng CA Meyer) is effective in the treatment of male ED and has been used as an alternative medication [4][5][6]. In a review of red ginseng-based treatment of ED, Jang et al [7] reported that randomized clinical studies have suggested therapeutic efficacy for red ginseng, but these studies typically do not have high methodological quality. Well-controlled clinical studies of Korean mountain ginseng have thus far not been performed, except for a preliminary report that claimed an effect of mountain ginseng extract on male ED [8].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] After numerous attempts have been made to assess the effectiveness of ginseng on ED, it has become increasingly evident that ginseng may be an effective agent therapy for ED. [9][10][11][12] The principal molecular ingredients responsible for the actions of ginseng are ginsenosides (also called ginseng saponins), which are amphiphilic molecules comprised of a hydrophobic aglycon backbone (a hydrophobic four-ring steroid-like structure) linked to hydrophilic carbohydrate side chains that consists of monomers, dimmers and tetramers. Ginsenosides were previously shown to influence several ion channels, such as voltage-dependent Ca 2 þ , Na þ channels, nicotinic acetylcholine receptors, N-methyl-D-aspartate receptors and large-conductance K Ca (BK Ca ) channels.…”
Section: Introductionmentioning
confidence: 99%